Theory Planned Behavior Dan Pengaruhnya Terhadap Kinerja Mahasiswa Dengan Coorporative Learning Tipe Jigsaw Sebagai Variabel Moderating Di FEB Universitas Muhammadiyah Surabaya - Siti Salbiyah (UMSurabaya Publishing, 2020)
The Theory of Planning Behavior Research (TPB) has a significant role in the performance of students with Jigsaw Cooperative Learning as a moderating variable. In this study, Cooperative Learning Type Jigsaw was chosen as moderating the relationship between Planned Behavior Theory (TPB) and student acquisition. The population used was 313 third semester students of management and accounting study program of FEB UM Surabaya. The sampling technique used is the Issac and Michael Tables to determine the sample size of 147 respondents. The analysis technique used is a Moderated Regression Analysis (MRA) analysis tool. The results of this research show (1) The Theory of Planned Behavior (TPB) does not significantly influence student performance, (2) Jigsaw Cooperative Learning does not moderate the effect of the Planned Behavior Theory (TPB) on student performance. Kata kunci :Theory Planned Behavior, Cooperative Learning Tipe Jigsaw, kinerja mahasiswa